1979
DOI: 10.1002/clc.4960020409
|View full text |Cite
|
Sign up to set email alerts
|

Concealed accessory pathway and dual av conduction: Drug‐dependent reentrant tachycardia

Abstract: Summary:Electrophysiological studies were performed in a patient with paroxysmal supraventricular tachycardia and a normal surface ECG at the time of the study. Premature atrial stimulation revealed dual AV conduction and an echo zone during AV conduction over the fast and the slow pathway. The prolongation of the AV conduction time by a calcium antagonist, Ro 11-1781, permitted the induction of tachycardias via both pathways. Premature ventricular stimulation yielded constant VA conduction times with activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1980
1980
1982
1982

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…Calcium antagonists like verapamil and tiapamil slow A -V conduction and, in extreme cases, may even cause sinus or A -V block. This mecha nism may explain the beneficial therapeutic effect o f verapamil [1,13] and tiapamil [3][4][5][6][14][15][16][17][18][19][20], Our experience w-ith tiapamil in pa tients with SVEs is consistent with the results published by other groups.…”
Section: Discussionsupporting
confidence: 82%
“…Calcium antagonists like verapamil and tiapamil slow A -V conduction and, in extreme cases, may even cause sinus or A -V block. This mecha nism may explain the beneficial therapeutic effect o f verapamil [1,13] and tiapamil [3][4][5][6][14][15][16][17][18][19][20], Our experience w-ith tiapamil in pa tients with SVEs is consistent with the results published by other groups.…”
Section: Discussionsupporting
confidence: 82%
“…These results are concordant with the electrophysiological studies by other groups [1][2][3] who have dem onstrated a prolongation of the A-H interval with constant H-V values. Our first results have been confirmed by therapeutic antiar rhythmic effects seen during and after surgery in patients with AF and tachyarrhythmias and in paroxysmal atrial tachycardia [4][5][6]. Dose-response studies have revealed that the administered dose of tiapamil is that re quired to achieve an antiarrhythmic effect with a reduction in A-V conduction rate [7.…”
Section: Discussionsupporting
confidence: 53%
“…3 c. d) [10]. This case has been published elsewhere and represents the un usual combination of dual antegrade A-V nodal conduction and a concealed accessory pathway [2], Circus movement reentry utiliz ing an accessory pathway was suggested by (a) capture of the atria with a ventricular extra stimulus during tachycardia when the His bundle was refractory (all patients) [7][8][9]11]; (b) increase in V-A interval during tachycar dia with functional bundle branch block ipsilateral to the extranodal accessory pathway (cases 2.4) [8]; (c) fixed V-A conduction time during premature ventricular pacing (all pa tients except case 3) [8], and (d) abnormal ret rograde atrial activation sequence during ta- …”
Section: Electrophysiologic Classification O F Arrhythmiamentioning
confidence: 99%
“…White syndrome [1][2][3][4], The present paper reviews our experience with intravenous tia pamil in patients with concealed accessory pathways.…”
Section: Introductionmentioning
confidence: 99%